Monitoring Tingkat Kekeruhan Air Pada Aquarium Budidaya Ikan Cupang - Fauziah Fauziah (Lembaga Pengembangan Kinerja Dosen, 2021)
Betta fish cultivation is currently in great demand, betta fish is one of the most popular ornamental fish in the world because of the beauty of its color and tail. There are still many betta fish maintenance who do not understand the importance of maintaining water conditions in the aquarium. Rapid technological developments can assist in the maintenance of betta fish using a microcontroller. This research designed a tool that can tell the user to replace cloudy aquarium water with new clean water without being monitored, then this tool can monitor the speed of incoming water and measure the amount of water that has been filled in the aquarium so it doesn't overflow. The tool uses two main sensors, namely a flow sensor and a turbidity sensor to check cloudy water conditions. Arduino Uno is a microcontroller that is used to control and process sensor input results and then display them using the LCD.